COLOR CHARACTERISTICS OF THE ANTERIOR TEETH IN DENTAL STUDENTS - Ilia Liondev; Ivet Dzhondrova; Rumen Radev; Dimitar Kirov; Elka Radeva; Rangel Todorov (Journal of IMAB)
Introduction: Tooth color is a key determinant of dental aesthetics and critically influences patient satisfaction. Traditional shade matching is subjective and inconsistent, while spectrophotometry offers standardized, reproducible, and objective measurements. Defining the natural color profiles of anterior teeth in young adults is essential for predictable and high-quality esthetic restorations. The purpose of this study is to analyze the color characteristics of the maxillary central incisors, lateral incisors, and canines in a population of young adults aged 18–21 using a spectrophotometer (Spectroshade; MHT Optic Research). Materials and Methods: Color measurements were conducted on 153 dental students aged 18–21 years using the SpectroShade Micro spectrophotometer. The teeth examined were maxillary central (11, 21), lateral incisors (12, 22) and canines (13, 23). VITA Classical shades were matched and subsequently converted to CIELAB values (L*, a*, b*). Statistical analysis included mean, SD, and one-way ANOVA (α = 0.05). Results: The central incisors had the highest L* (lightness) values, indicating greater brightness. Canines presented significantly higher b* values, reflecting more pronounced yellowness. Statistically significant differences (p < 0.05) were observed among the tooth groups. Conclusion: Color parameters of anterior teeth vary significantly between tooth types in young adults. These findings are valuable for aesthetic restorative procedures and provide a reference for shade selection in this age group.